The effectiveness of e-learning in light of the spread of the Corona virus from the point of view of teachers in public schools in Palestine - Rabay’a, Ra’eda Abed al- Rahman (Journal of Educational and Psychological Sciences, 2022)
This study aimed to reveal the effectiveness of e-learning in light of the spread of the Corona virus from the point of view of teachers in public schools in Palestine.To achieve the objectives of the study, the descriptive analytical approach was relied.The study sample consisted of (50) English language teachers in public schools in Palestine who were taught during the spread of the Corona virus through the e-learning system.The necessary data were collected using a questionnaire whose reliability coefficient was (0.804) and was applied to the study sample. The results of the study revealed that the study sample’s evaluation of the effectiveness of e-learning in light of the spread of the Corona virus from their point of view was reached (2.45) with a medium degree. The researchers recommended holding training courses in the field of e-learning for both teachers and students and to help get rid of all obstacles that prevent benefiting from the e-learning system followed, and the need to combine face- to- face education and e- education in higher education institutions in the future.
Keywords: e-learning; public schools in Palestine; coronavirus